2021
DOI: 10.1093/europace/euaa415
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between procedural volume and complication rates for catheter ablation of atrial fibrillation: a systematic review and meta-analysis

Abstract: Aims There are conflicting data as to the impact of procedural volume on outcomes with specific reference to the incidence of major complications after catheter ablation for atrial fibrillation. Questions regarding minimum volume requirements and whether these should be per centre or per operator remain unclear. Studies have reported divergent results. We performed a systematic review and meta-analysis of studies reporting the relationship between either operator or hospital atrial fibrillati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…The finding of a threshold in the range of 150-200 procedures per year, is in keeping with previous work suggesting benefits in excess of 100 procedures per year. 5 In addition, the present study sheds new light on the effect of ablation type on this relationship. In keeping with the recognition that cryoablation appears to offer an easier learning curve, the effect of procedural volume on both safety and efficacy outcomes was eliminated when considering only cryoablation cases.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The finding of a threshold in the range of 150-200 procedures per year, is in keeping with previous work suggesting benefits in excess of 100 procedures per year. 5 In addition, the present study sheds new light on the effect of ablation type on this relationship. In keeping with the recognition that cryoablation appears to offer an easier learning curve, the effect of procedural volume on both safety and efficacy outcomes was eliminated when considering only cryoablation cases.…”
mentioning
confidence: 67%
“…The relationship between AF ablation volume and outcomes has been explored in previous studies. 4,5 Tonchev et al, in a meta-analysis, demonstrated a significantly lower risk of complications in centers performing >100 procedures per year (odds ratio [OR]: 0.62, 95% confidence interval [CI]: 0.53-0.73). 4 This carried over to mortality, which was significantly lower in high volume centers (OR: 0.33, 95% CI: 0.26-0.43).…”
mentioning
confidence: 99%
“…An earlier study reported that hospitals with an annual CA volume of <50 or <100 cases were significantly associated with acute complications. 14,15 Another study investigating acute complications and 30-day rehospitalization after CA for AF reported that recent hospital experience was associated with a higher risk of adverse outcomes. 7 Although the ablation technique and catheter system of these previous studies, which used data acquired before 2010, differed from those of the current study, these previous results are consistent with those of the current study, which showed that the annual case volume was inversely associated with the occurrence of acute complications.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the impact of radiofrequency ablation versus that of cryoballoon ablation based on procedural volume was insufficient in other studies. 14,15 Some studies have shown that the cryoballoon ablation procedure is simple and safe, with a shorter procedure time than that for radiofrequency ablation. 3,24 Compared with cryoballoon ablation, radiofrequency ablation can more readily be applied to patients with persistent and long-standing AF and nonpulmonary vein triggers 12 ; however, the learning curve to develop radiofrequency ablation skills is considerable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation